Victor S. Clark papers - Clark, Victor S. (Victor Selden), 1868-1946.
Correspondence, reports on countries and regions, notes, family papers, clippings, and other papers pertaining primarily to Clark's career as an economist and author. Documents his work as trustee of the Institute of Current World Affairs, member of the Board of Research Associates in American Economic History of the Carnegie Institution of Washington, arbitrator on railroad cases with the U.S. Bureau of Mediation, and member of the Insular Board of Education in Puerto Rico shortly after the territory was acquired by the United States in 1898. Correspondents include Thomas L. Blakemore, Hallie Flanagan, John N. Hazard, Walter S. Rogers, and Phillips Talbot.
Family papers contain farm diaries, business and land records, account books, daybooks, and financial records and legal papers relating to the firm of Green and Davis, Levi Davis, LeRoy Davis, and the Davis and Clark families especially in the Genesse River Valley, New York.
Economist and author.
Collection material in English and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blakemore, Thomas L., -- 1915- -- Correspondence; Davis, LeRoy, -- 1836-1928.; Davis, Levi, -- 1807-1884.; Flanagan, Hallie, -- 1890-1969 -- Correspondence; Hazard, John N. -- 1909-1995 -- Correspondence; Rogers, Walter S. -- Correspondence; Talbot, Phillips -- Correspondence; Clark family; Davis family; Puerto Rico. -- Insular Board of Education; United States. -- Bureau of Mediation; Board of Research Associates in American Economic History; Institute of Current World Affairs; Green and Davis; Agriculture -- New York (State); Economics; Education -- Puerto Rico; Merchants -- New York (State); Railroads -- United States; Economic history; Social history; World politics; Genesee River Valley (Pa. and N.Y.) -- History; Genesee River Valley (Pa. and N.Y.) -- Social life and customs; New York (State) -- History; Authors; Economists